Is it Worth the Effort? Novel Insights into Obesity-Associated Alterations in Cost-Benefit Decision-Making - Mathar, David; Horstmann, Annette; Pleger, Burkhard; Villringer, Arno; Neumann, Jane (Frontiers in Behavioral Neuroscience, 2016)
Cost-benefit decision-making entails the process of evaluating potential actions according to the trade-off between the expected benefit (reward) and the anticipated costs (effort). Recent research revealed that dopaminergic transmission within the fronto-striatal circuitry strongly modulates cost-benefit decision-making. Alterations within the dopaminergic fronto-striatal system have been associated with obesity, but little is known about cost-benefit decision-making differences in obese compared with lean individuals. With a newly developed experimental task we investigate obesity-associated alterations in cost-benefit decision-making, utilizing physical effort by handgrip-force exertion and both food and non-food rewards. We relate our behavioral findings to alterations in local grey matter volume assessed by structural MRI. Obese compared with lean subjects were less willing to engage in physical effort in particular for high-caloric sweet snack food. The amount of effort exertion was thereby negatively associated with subjects’ individual levels of chronic stress and punishment sensitivity. Further, self-reported body dissatisfaction negatively correlated with the willingness to invest effort for sweet snacks in obese men. On a structural level, obesity was associated with reductions in grey matter volume in bilateral prefrontal cortex. Nucleus accumbens volume positively correlated with task-induced implicit food craving. Our results challenge the common notion that obese individuals are willing to work harder to obtain high-caloric food and emphasize the need for further exploration of the underlying neural mechanisms regarding cost-benefit decision-making differences in obesity.